Epidemiology of acute kidney injury in critically ill patients: the multinational AKI-EPI study - Hoste, Eric A. J.; Bagshaw, Sean M.; Bellomo, Rinaldo; Cely, Cynthia M.; Colman, Roos; Cruz, Dinna N.; Edipidis, Kyriakos; Forni, Lui G.; Gomersall, Charles D.; Govil, Deepak; Honoré, Patrick M.; Joannes-Boyau, Olivier; et al. (Intensive care medicine, 2015)
Purpose Current reports on acute kidney injury (AKI) in the intensive care unit (ICU) show wide variation in occurrence rate and are limited by study biases such as use of incomplete AKI definition, selected cohorts, or retrospective design. Our aim was to prospectively investigate the occurrence and outcomes of AKI in ICU patients. Methods The Acute Kidney Injury–Epidemiologic Prospective Investigation (AKI-EPI) study was an international cross-sectional study performed in 97 centers on patients during the first week of ICU admission. We measured AKI by Kidney Disease: Improving Global Outcomes (KDIGO) criteria, and outcomes at hospital discharge. Results A total of 1032 ICU patients out of 1802 [57.3 %; 95 % confidence interval (CI) 55.0–59.6] had AKI. Increasing AKI severity was associated with hospital mortality when adjusted for other variables; odds ratio of stage 1 = 1.679 (95 % CI 0.890–3.169; p = 0.109), stage 2 = 2.945 (95 % CI 1.382–6.276; p = 0.005), and stage 3 = 6.884 (95 % CI 3.876–12.228; p < 0.001). Risk-adjusted rates of AKI and mortality were similar across the world. Patients developing AKI had worse kidney function at hospital discharge with estimated glomerular filtration rate less than 60 mL/min/1.73 m 2 in 47.7 % (95 % CI 43.6–51.7) versus 14.8 % (95 % CI 11.9–18.2) in those without AKI, p < 0.001. Conclusions This is the first multinational cross-sectional study on the epidemiology of AKI in ICU patients using the complete KDIGO criteria. We found that AKI occurred in more than half of ICU patients. Increasing AKI severity was associated with increased mortality, and AKI patients had worse renal function at the time of hospital discharge. Adjusted risks for AKI and mortality were similar across different continents and regions.